Social, technical and institutional innovation: oil palm smallholders’ responses to rising land and income pressures in Papua New Guinea - Nake Steven; Curry George N.; Koczberski Gina; Germis Emmanuel; Bue Veronica; Tilden Geraldine M.; Koia Merolyn; Pileng Linus; Ryan Sean (Cahiers Agricultures)
This paper discusses how smallholder settlers on government-sponsored oil palm land settlement schemes in West New Britain Province, Papua New Guinea, have responded to rising land pressures since the late 1960s when the settlement schemes were established. After providing an overview of the oil palm industry in Papua New Guinea and key smallholder groups, the paper focuses on how settlers responded to land and income pressures through technical, social and institutional innovations. It is argued that while smallholders have experienced significant constraints and threats to their livelihoods, most have been able to exercise a fair degree of agency to improve their livelihoods. Institutional factors have also been critical to enhancing smallholders’ adaptive capacity in responding to rising land and economic pressures.